2015
DOI: 10.3354/meps11314
|View full text |Cite
|
Sign up to set email alerts
|

Sub-tropical seagrass ecosystem metabolism measured by eddy covariance

Abstract: The metabolism of seagrass ecosystems was examined at 4 sites in south Florida, USA, using the eddy covariance technique under in situ conditions. Three sites were located across a phosphorus-driven productivity gradient to examine the combined effects of dynamic variables (irradiance, flow velocity) and state variables (sediment phosphorus and organic content, seagrass biomass) on ecosystem metabolism and trophic status. Gross primary production and respiration rates varied significantly across Florida Bay in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 65 publications
5
49
0
Order By: Relevance
“…Berg & Huettel 2008 has proven itself as a very powerful, non-invasive technique for resolving benthic O 2 ex change and metabolism in challenging coastal environments (e.g. Glud et al 2010, Attard et al 2014, Long et al 2015. The approach, however, will only work during inundation, but combined application of AEC and continuous auto nomous in situ microprofiling measurements, as realized here, might represent an ideal procedure for resolving NEM in dynamic intertidal settings and to assess the importance of such environments for marine carbon cycling in general.…”
Section: Cross-study Comparisons Of Nem In Intertidal Sedimentsmentioning
confidence: 99%
“…Berg & Huettel 2008 has proven itself as a very powerful, non-invasive technique for resolving benthic O 2 ex change and metabolism in challenging coastal environments (e.g. Glud et al 2010, Attard et al 2014, Long et al 2015. The approach, however, will only work during inundation, but combined application of AEC and continuous auto nomous in situ microprofiling measurements, as realized here, might represent an ideal procedure for resolving NEM in dynamic intertidal settings and to assess the importance of such environments for marine carbon cycling in general.…”
Section: Cross-study Comparisons Of Nem In Intertidal Sedimentsmentioning
confidence: 99%
“…Over the last 10 years, the aquatic eddy covariance technique has become a widely accepted approach for measuring oxygen fluxes between benthic ecosystems and the overlying water . In that time, the number of users has grown rapidly, and the technique has been applied under very different field settings such as muddy and sandy sediments Kuwae et al, 2006;Glud et al, 2010), deep ocean sediments (Berg et al, 2009), coral reefs Cathalot et al, 2015;Rovelli et al, 2015), and seagrass meadows (Hume et al, 2011;Rheuban et al, 2014;Long et al, 2015). With a few exceptions, all of the recently published aquatic eddy covariance studies have focused on oxygen fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike in incubations, saturation occurred for a complete meadow under low in situ light conditions. It contrasts with light-limitation of mature Z. marina and T. testudinum meadows under in situ irradiance (Rheuban et al 2014;Long et al, 2015), and suggests that a factor other than light may limit primary production at peak irradiance. Nutrient limitation may contribute.…”
Section: Flux-irradiance Curvesmentioning
confidence: 78%
“…Therefore, the decomposition of leaf litter within the ecosystem was substantially smaller than production. Prior studies utilizing the eddy covariance technique in summer identified greatrer similarity between respiration and 230 primary production in Zostera marina meadows in the mid-Atlantic Bight (Rheuban et al, 2014a) and in Thalassia testudinum meadows in Florida Bay, USA (Long et al, 2015). In those studies NEM was one-fifth of GPP.…”
Section: Seagrasses Versus Sandsmentioning
confidence: 99%
See 1 more Smart Citation